2004
DOI: 10.1046/j.0022-202x.2004.22208.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Diagnosis by Raman Spectroscopy and Neural Networks: Structure Alterations in Proteins and Lipids in Intact Cancer Tissue

Abstract: Melanoma is the most aggressive skin cancer. The specificity and sensitivity of clinical diagnosis varies from around 40% to 80%. Here, we investigated whether the chemical changes in the melanoma tissue detected by Raman spectroscopy and neural networks can be used for diagnostic purposes. Near-infrared Fourier transform Raman spectra were obtained from samples of melanoma (n=22) and other skin tumors that can be clinically confused with melanoma: pigmented nevi (n=41), basal cell carcinoma (n=48), seborrheic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
231
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(250 citation statements)
references
References 47 publications
14
231
1
4
Order By: Relevance
“…Other studies have also shown the ability of Raman spectroscopy to accurately classify diseased tissue in brain, 16,17 skin, [18][19][20][21][22][23][24] cervix, [25][26][27] breast, 1,2,9,10,28-33 and other organs. 8,11,[34][35][36][37][38][39][40][41][42][43][44] Our data is confirmatory, and, in addition, demonstrates changes in the tumor bed, which probably represent the detection of chemical signs of preneoplastic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown the ability of Raman spectroscopy to accurately classify diseased tissue in brain, 16,17 skin, [18][19][20][21][22][23][24] cervix, [25][26][27] breast, 1,2,9,10,28-33 and other organs. 8,11,[34][35][36][37][38][39][40][41][42][43][44] Our data is confirmatory, and, in addition, demonstrates changes in the tumor bed, which probably represent the detection of chemical signs of preneoplastic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors discussed, based on these observations, that the neoplastic transformation in the tissues, can start cellular changes no matter FIGURE 3 -The discriminative analysis of data was able to differ 93.1% of the variables. Through two imaginary lines, the separation of the groups by similarity can be observed the kind of tissue involved and the alterations on the amide bands in the Raman spectra are attributed to the protein conformation 10 . In the melanoma group of this study, the alterations visually examined were similar, diminishing on the Amide I band, with spectral area distortion between 1640 and 1670 cm -1 .…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55] The first processing step involves background subtraction whereby a dark spectrum is subtracted from the raw spectrum. Second, the wavelength and intensity calibrations are performed in a very similar manner as described for the fluorescence spectra; the only difference is that the peak fitting algorithm is used to find Tylenol pixel locations (instead of HgAr lines as needed for the fluorescence).…”
Section: Ramanmentioning
confidence: 99%